Antidyslipidemic potential of a novel farnesoid X receptor antagonist in a hamster model of dyslipidemia: Comparative studies of other nonstatin agents. Issue 2 (8th March 2018) - Shinozawa, Emiko; Amano, Yuichiro; Yamakawa, Hiroko; Haba, Megumi; Shimada, Mitsuyuki; Tozawa, Ryuichi
Abstract: We attempted to clarify the therapeutic capability of antagonists of the farnesoid X receptor (FXR), a nuclear receptor that regulates lipid and bile acid metabolism. Herein, we report the antidyslipidemic effects of a novel synthesized FXR antagonist, compound‐T1, utilizing a dyslipidemic hamster model. Compound‐T1 selectively inhibited chenodeoxycholic acid‐induced FXR activation (IC50, 2.1 nmol·L −1 ). A hamster model of diet‐induced hyperlipidemia was prepared to investigate the antidyslipidemic effects of compound‐T1 through comparative studies of the nonstatin lipid‐modulating agents ezetimibe, cholestyramine, and torcetrapib. In the hamster model, compound‐T1 (6 mg·kg −1 ·day −1, p.o.) increased the level of plasma high‐density lipoprotein (HDL)‐cholesterol (+22.2%) and decreased the levels of plasma non‐HDL‐cholesterol (−43.6%) and triglycerides (−31.1%). Compound‐T1 also increased hepatic cholesterol 7α‐hydroxylase expression and fecal bile acid excretion, and decreased hepatic cholesterol content. Moreover, the hamster model could reflect clinical results of other nonstatin agents. Torcetrapib especially increased large HDL particles compared with compound‐T1. Additionally, in the human hepatoma Huh‐7 cells, compound‐T1 enhanced apolipoprotein A‐I secretion at a concentration close to its IC50 value for FXR. Our results indicated the usefulness of the hamster model in evaluating FXR antagonists and nonstatin agents. Notably, compound‐T1 exhibited beneficial effects on both blood non‐HDL‐cholesterol and HDL‐cholesterol, which are thought to involve enhancement of cholesterol catabolism and apolipoprotein A‐I production. These findings aid the understanding of the antidyslipidemic potential of FXR antagonists with a unique lipid and bile acid modulation.